Determinant attributes of city brand personality that influence strategic communication - Ahmad, Muhamad Fazil; Abdullah, Zulhamri; Tamam, Ezhar; Bolong, Jusang (Canadian Academy of Oriental and Occidental Culture, 2013)
This paper examines the determinant attributes of city brand personality that influence strategic communication of Bandar Melaka world heritage city UNESCO. The results will provide insight on the development of a city brand personality scale, that can be applied in the Malaysian context. Based on Aaker (1997), Brand Personality Scale (BPS), the study adjusted the scale used in the Bandar Melaka for strategic communication. The study approaches the issues from several perspectives including the marketing, tourism, strategic management and human communication in Bandar Melaka. It employs to administer the process of structural equation modelling to investigate the causal relationships between the dimensions of city brand determinants and city brand itself for strategic communication. Questionnaire surveys and interviews on measuring the determinants of city brand employs to examine the respondents’ perceptions of the dimensions of city brand affected the overall city brand evaluations. Data collects from the internal stakeholders that involving directly or indirectly for planning and developing of Bandar Melaka. The study has found four dimensions of the city brand personality, “Peacefulness”, “Malignancy”, “Sophistication” and “Uniqueness”. The City Personality Scale (CPS) proposes four dimensions with a total of seventeen items can be applied to the communication perspective of city brand in Malaysia. Implications for the stakeholders were discussed. They should consider the relative importance of brand dimensions in their overall city brand evaluations for strategic communication. City brand plays a pivotal role in contemporary strategic communication, and is the subject of much literature, both professional and academic. This study is perhaps one of the first to investigate city brand personality for strategic communication in Malaysia.